FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI MASYARAKAT PADA BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN GIANYAR - Eka Yani, Ni Putu Rita; Sudibia, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 8 (2020): VOL 9 NO 8, AGUSTUS 2020 (1631 - 1887), 2020)
The purpose of this study is (1) analyze the effect of service quality, income and innovation simultaneously on people's buying interest in BUMDes in Gianyar Regency, (2) analyze the effect of service quality, income and innovation partially on people's buying interest in BUMDes in Gianyar Regency, and (3) analyze the variables that have a dominant influence between service quality, income and innovation on people's buying interest in BUMDes in Gianyar Regency. The number of samples is 90 with the asidental sampling method. Data collection is done through observation, structured interviews and in-depth interviews. The analysis technique used is multiple linear analysis techniques and the software used is SPSS. The results showed that (1) Variable service quality, income and innovation simultaneously had a significant effect on people's buying interest in Village Owned Enterprises (BUMDes) in Gianyar Regency, (2) Service quality, income and innovation variables had a partially positive and significant effect on community buying interest in Village-Owned Enterprises (BUMDes) in Gianyar Regency (3) Innovation variable is the most dominant factor influencing community buying interest in Village-Owned Enterprises (BUMDes) in Gianyar Regency, this can be seen from the absolute value of standardized coefficients beta which is higher than other variables. Keywords : buying interest, service quality, income and innovation